Detection and Characterization of Early Gastric Cancer - Ferreira, Carlos Noronha; Serrazina, Juliana; Marinho, Rui Tato (Frontiers in Oncology, 2022)
In this review, we would like to focus on risk stratification and quality indicators of diagnostic upper gastrointestinal endoscopy in the detection and characterization of early gastric cancer. Preparation of the upper gastrointestinal tract with mucolytic agents or simethicone is often overlooked in the west, and this inexpensive step prior to endoscopy can greatly improve the quality of imaging of the upper digestive tract. Risk stratification based on epidemiological features including family history, Helicobacter pylori infection status, and tobacco smoking is often overlooked but may be useful to identify a subgroup of patients at higher risk of developing gastric cancer. Quality indicators of diagnostic upper gastrointestinal endoscopy are now well defined and include: minimal inspection time of 3 min, adequate photographic documentation of upper gastrointestinal landmarks, utilization of advanced endoscopic imaging technology including narrow band imaging and blue laser imaging to detect intestinal metaplasia and characterize early gastric cancer; and standardized biopsy protocols allow for histological evaluation of gastric mucosa and detection of atrophic gastritis and intestinal metaplasia. Finally, endoscopic and histologic classifications such as the Kimura–Takemoto Classification of atrophic gastritis and the OLGA–OLGIM classifications may help stratify patients at a higher risk of developing early gastric cancer.